Cover Feature: A Forkhead Box Protein C2 Inhibitor: Targeting Epithelial–Mesenchymal Transition and Cancer Metastasis (ChemBioChem 13/2018). (7th June 2018) - Castaneda, Maria; Chen, Luxi; Pradhan, Lagnajeet; Li, Shichang; Zein, Ruba; Lee, Yeongju; Lim, Hyun‐Suk; Nam, Hyun‐Joo; Lee, Jiyong
Abstract : The cover feature picture shows MC‐1‐F2, the first small‐molecule inhibitor of forkhead box protein C2 (FOXC2). FOXC2 is known to be necessary for initiating and maintaining the epithelial–mesenchymal transition (EMT), a critical process of cancer metastasis. A bicycle with square wheels illustrates the cancer cells whose metastatic move was halted due to the reversal of EMT by MC‐1‐F2. More information can be found in the communication by J. Lee et al. onpage 1359 in Issue 13, 2018 (DOI:10.1002/cbic.201800022 ).